RACE DETERMINATION FROM METRIC AND NON-METRIC METHODS IN CRANIUM - Anna Nur Azizah (Journal of Health and Dental Sciences, 2026)
Race or ancestry estimation plays a crucial role in forensic anthropology for identifying unknown individuals through skeletal analysis. The cranium, as the most diagnostic part of the skeleton, provides essential morphological indicators that vary among racial groups. This literature review aims to summarize current findings on race determination using both metric and non-metric methods of the cranium. Metric analysis relies on quantitative anthropometric measurements such as cephalic and nasal indices, while non-metric analysis focuses on morphological traits including nasal aperture shape, zygomatic arch prominence, palatal form, and the presence of torus palatinus. Various studies indicate that combining both methods yields more reliable results compared to using either alone. Although no single cranial feature can definitively determine race, a combination of multiple cranial and dental traits enhances the accuracy of ancestry estimation. Repeated measurements and observer agreement are necessary to minimize subjective bias and improve forensic reliability. This article review will describe race determination from the cranium in the odontology field. DOI : 10.54052/jhds.v5n3.p253-266